ASGM status in West Nusa Tenggara Province, Indonesia - Baiq Dewi Krisnayanti (Journal of Degraded and Mining Lands Management, 2018)
Artisanal Small-Scale Gold Mining (ASGM) obviously contributes to serious environmental and health issue for miners, nearby populations, and larger community when the use of mercury (Hg) occurs.  Mercury amalgamation is used as a gold recovery technique by 10-12 million ASGM miners around the world and a predicted around 1000 tons of mercury are discharged into the environment every year as a result of poor mining practices. Exposure to mercury can cause serious health effects for future generation, and miners and their families are vulnarable group to expose with mercury vapor and methyl mercury contaminated food in ASGM areas, resulting in increase of levels of mercury in human specimens. Thus, investigate the the effects of mercury on the environment and people health are urgently necessary for developing a better solution to eliminate further mercury contamination to environment in West Nusa Tenggara (WNT) Province. A field survey had been conducted for this research in two main ASGM spots in WNT Province: Sekotong-Lombok island and Taliwang-Sumbawa island. As part of the study, an initial health survey and socio-economic of workers/miners was conducted. Volunteer participants at sampling locations across Sekotong-Lombok and Taliwang-Sumbawa (exposed; indirect exposed; non exposed groups) answered a questionnaire, and allowed the sampling of hair for subsequent analysis. The ore, tailing, plants and soil samples were also collected for investigating Hg concentration on the substances. The results found that the impact of ASGM on increasing  economic activity leading to jobs, income and opportunities for social development is positive. However, there is risk of contamination in soil and plants environment through mining activity and high Hg concentration discovered in human body in a short time of ASGM activity. The environmental sustainability of mining can be better regulated within legalised areas. Environmental monitoring will define unacceptable risk and allow for advanced implementation of remedial measures before an uncontrollable disaster occurs.